Challenges and strategies of clinical rounds from the perspective of medical students: A qualitative research - Amin Beigzadeh; Nikoo Yamani; Kambiz Bahaadinbeigy; Peyman Adibi (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Clinical rounds provide opportunities for medical students to acquire essential skills to practice medicine in the real world. Although this kind of training is one of the most important components of medical education, it is replete with barriers in its effective implementation. This study aimed to investigate medical students' experiences concerning the barriers and strategies of clinical rounds in Kerman University of Medical Sciences (KMU). MATERIALS And METHODS: This qualitative research was conducted on 12 medical students in KMU in 2017. Purposive sampling was used and participants in three grades (stagers, interns, and residents) were selected, and individual semi-structured interviews were conducted until data saturation. The average of the interview time differed among the three batches (stagers, 51 min; interns, 38 min; and residents, 31 min). Content analysis using deductive approach was used for data analysis. MAXQDA version 10 was used for data analysis. RESULTS: Data analysis yielded the identification of six themes related to the system of clinical education, fields of clinical education, clinical environment, educational program, medical teachers, and medical students concerning the barriers and five themes related to the strategies for clinical rounds. CONCLUSIONS: Findings revealed a deeper understanding of medical students' experiences. Our investigation identified multiple challenges embedded in our context and strategies to overcome them. As teaching in clinical rounds is invaluable, there is a need to take into account the identified challenges and overcome them. Thus, more effective rounds with higher efficacy toward students' professional development can be implemented.